EFEKTIVITAS MEDIASI SEBAGAI ALTERNATIF PENYELESAIAN KASUS KEKERASAN DALAM RUMAH TANGGA - M.Chalid, M.Chalid; Adnan, Idul (PRODI HUKUM TATANEGARA, 2024)
This research aims to analyze the effectiveness of mediation as an alternative resolution for domestic violence cases. The primary objective of this research is to evaluate how mediation can provide a supportive and constructive environment for resolving conflicts between victims and perpetrators, while also promoting healing and restoration of relationships. The research employs qualitative methods, utilizing interviews and case studies as data collection techniques to gather insights from mediators, victims, and relevant stakeholders. The findings indicate that mediation can significantly reduce tension and foster communication between parties, leading to more amicable resolutions compared to traditional judicial processes. However, challenges such as power imbalances and the need for trained mediators remain critical factors influencing the success of mediation in domestic violence cases. This research highlights the potential of mediation to serve as an effective tool in addressing domestic violence, while also calling for improved training and support systems for mediators involved in such sensitive matters